Penguasaan kosa kata asas Bahasa Melayu di dalam kalangan murid tahun satu di Sekolah Siam Ban Khorlogaway, Narathiwat: Kajian kes / Nurhuda @ Nurul Huda Chedo - Nurhuda @ Nurul Huda, Chedo (2012)
This study aimed at studying the acquisition of basic Malay language vocabulary, specifically the basic reading among the students of Year I at Siamese School Ban Khorlokaway, in the district of Sri Sakorn, Narathiwat, Southern Thailand. Among the objectives of this study is to analyse the level of abi lity to acquire the basic vocabulary in the language of students in their Year I, to establish the reading skill of Year I students in comprehending what was being read and to verify the related attributing factors with the problems in their acqus ition of basic vocabulary of the students in Year 1. This is an initial studies done at Siamese School specifically among the Year I pupuls to estab lish their competency level of the basic reading ski ll in Malay language carried out using the Basic Reading Module Year I (Edition 1) as scale. The subjects for this study were 30 Year I students in the age range of 7 year old, of Malay decents who use their mother tongue, that is, the Malay language in the Pattani dialect, but are not using the Malay language in their daily communication, that is in the Thai language. The subjects of this study never use Malay language before, thus they have no basic knowledge of the Malay language. The study is carried out through drill practices, individually or in batches and groups. The test were carried out twice through prereading and post reading activities. Before the tests were carried out during the post reading after process reading (P&P) the subjects were taught twice for all skills fo llowed by test. The studies was carried out through observation, reviews, and interviews carried out on subjects, the Malay language teachers and parents. Data collected through the pupils abi lity records were analysed and findngs concluded. The results on the tests carried out on subjects pointed out that half of the subj ects studied could acquired very well at the basic Malay language vocabulary at the identification of alphabets, but a big majority of the subject studied satisfactorily acquired the phonic skills, words application, phrases and followed by sentence skills. This group could not acquire these skills satisfactori ly. However, this study proved that 3 pupils (about 10 percent) of the subjects cou ld acqu ire very well the Module 1 of Basic Reading Year 1 (Edition 1) and this pupils achieved full marks of I 00 percent at the testing stage after the P&P process, that is, they could read with ease and could comprehend very what they read. The factors that impede their acquistion among others are short time spent, the leraning enviroment which was not suitable, the influence of the Thai Language and their mother tongue, and the low motivational drive towrds the Malay language. These sa id factors brought about these difficulties and thus should be overcome by all stake holders assosciated in the study carried out. It is hoped that all stake holders on learning this outcome could play prominent roles in rectifying the difficulties faced among students in their acquired reading skills.